2020
DOI: 10.3389/fonc.2020.00867
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Oncogenic Driver in a Lung Adenocarcinoma Patient Harboring an EGFR-KDD and Response to Afatinib

Abstract: Introduction: Oncogenic mutations in the epidermal growth factor receptor (EGFR) occur frequently in patients with lung cancer. These mutations may serve as critical predictive biomarkers in patients with non-small cell lung cancer (NSCLC). Among them, EGFR exon 18-25 kinase domain duplication (EGFR-KDD) mutations have been identified as a novel EGFR gene subtype in NSCLC. Case Presentation: We reported a rare case of a 59-year-old male diagnosed with adenocarcinoma. A biopsy revealed an EGFR-KDD identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Preclinical data demonstrate that EGFR -KDD confers constitutive activity to the EGFR tyrosine kinase and sensitivity to EGFR-TKIs including erlotinib, afatinib, and osimertinib ( 8 ). Several instances of clinical evidence have revealed the efficacies of EGFR-TKIs in advanced LUAD but yielded variable antitumor responses ( 8 11 ). The first case of EGFR -KDD in LUAD is reported by Gallant et al where a 33-year-old male smoker diagnosed with stage IV LUAD did not carry any common EGFR mutations but achieved PR after being treated with afatinib ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical data demonstrate that EGFR -KDD confers constitutive activity to the EGFR tyrosine kinase and sensitivity to EGFR-TKIs including erlotinib, afatinib, and osimertinib ( 8 ). Several instances of clinical evidence have revealed the efficacies of EGFR-TKIs in advanced LUAD but yielded variable antitumor responses ( 8 11 ). The first case of EGFR -KDD in LUAD is reported by Gallant et al where a 33-year-old male smoker diagnosed with stage IV LUAD did not carry any common EGFR mutations but achieved PR after being treated with afatinib ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first case of EGFR -KDD in LUAD is reported by Gallant et al where a 33-year-old male smoker diagnosed with stage IV LUAD did not carry any common EGFR mutations but achieved PR after being treated with afatinib ( 8 ). Stable disease (SD) response to afatinib was observed in a 59-year-old patient with LUAD ( 11 ). Furthermore, studies have also documented that patients with EGFR -KDD-positive LUAD showed response to first-generation EGFR-TKI icotinib and third-generation EGFR-TKI osimertinib ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…NGS of a tumor specimen obtained after erlotinib therapy did not reveal a potential resistance mechanism, including the EGFR T790M mutation. The limited data available for the treatment of NSCLC patients with EGFR‐KDD has shown that it is sensitive to several EGFR‐TKIs 3–11 . Preclinical studies showed that afatinib inhibited the growth of cells expressing an EGFR‐KDD form of the receptor and that cetuximab further enhanced the activity of afatinib 6,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that most conventional sequencing platforms or PCR‐based methods do not routinely detect EGFR alterations affecting introns, such screening procedures may miss some patients who would benefit from targeted therapy. We reviewed 19 EGFR‐KDD patients from seven studies and the case reported here ( n = 20 in total) in order to investigate who should further be examined for EGFR‐KDD 3–7,9,10 . Patient ages ranged from 33–87 (median, 59.5), and 12/21 (57.1%) patients were male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation